Inverse geometry design of two-dimensional complex radiative enclosures using krill herd optimization algorithm - Sun, Shuangcheng; Qi, Hong; Zhao, Fangzhou; Ruan, Liming; Li, Bingxi (Applied thermal engineering, 2016)
•KH achieves better performance in solving the inverse geometry design problems.•The extinction coefficient has significant impact on the inverse design results.•The scattering property and emissivity mainly affect radiative heat flux. [Display omitted] The krill herd (KH) algorithm is used to solve the inverse geometry design of a two-dimensional radiative enclosure filling with participating media. This inverse design problem aims to satisfy a uniform distribution of radiative heat flux over the design surface. The forward radiative heat transfer problem in irregular enclosures is solved by using the discrete ordinate method with a body-fitted coordinate system. Consequently, five kinds of KH algorithms are utilized to optimize the geometric positions of the control points, and Akima cubic interpolation is used to approximate the changing boundary through these points. Retrieval results show that the KH algorithm can be applied successfully to inverse geometry design problems, and KH is proved to be more efficient than the micro genetic algorithm and particle swarm optimization algorithms. The influences of radiative properties of the media and the number of control points on the retrieval geometry design results are also investigated.